Anticonvulsant Essential Oils and Their Relationship with Oxidative Stress in Epilepsy - da Fonsêca, Diogo Vilar (Biomolecules, 2019)
Epilepsy is a most disabling neurological disorder affecting all age groups. Among the various mechanisms that may result in epilepsy, neuronal hyperexcitability and oxidative injury produced by an excessive formation of free radicals may play a role in the development of this pathology. Therefore, new treatment approaches are needed to address resistant conditions that do not respond fully to current antiepileptic drugs. This paper reviews studies on the anticonvulsant activities of essential oils and their chemical constituents. Data from studies published from January 2011 to December 2018 was selected from the PubMed database for examination. The bioactivity of 19 essential oils and 16 constituents is described. Apiaceae and Lamiaceae were the most promising botanical families due to the largest number of reports about plant species from these families that produce anticonvulsant essential oils. Among the evaluated compounds, β-caryophyllene, borneol, eugenol and nerolidol were the constituents that presented antioxidant properties related to anticonvulsant action. These data show the potential of these natural products as health promoting agents and use against various types of seizure disorders. Their properties on oxidative stress may contribute to the control of this neurological condition. However, further studies on the toxicological profile and mechanism of action of essential oils are needed.